2002
DOI: 10.1002/jos.121
|View full text |Cite
|
Sign up to set email alerts
|

Scheduling chains on uniform processors with communication delays

Abstract: SUMMARYWe show that the problem of scheduling chains of unit execution time (UET) jobs on uniform processors with communication delays to minimize makespan is NP-hard in the strong sense. We also give a heuristic that generates solutions with known, and relatively small, absolute error for this problem. The NP-hardness result holds even for the case without communication delays, and complements the earlier result of Gonzalez and Sahni who gave a polynomial time algorithm for preemptive jobs of arbitrary length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…So, N P-completeness of BSSP is not trivial. Trystram et al proved N P-completeness of scheduling independent chains under the BSP model [14], [18]. This proof implies N P-completeness of BSSP in the case of scheduling independent chains.…”
Section: Proofs Of N P-completeness and Nonapproximabilitymentioning
confidence: 69%
“…So, N P-completeness of BSSP is not trivial. Trystram et al proved N P-completeness of scheduling independent chains under the BSP model [14], [18]. This proof implies N P-completeness of BSSP in the case of scheduling independent chains.…”
Section: Proofs Of N P-completeness and Nonapproximabilitymentioning
confidence: 69%
“…Kubiak, Penz and Trystram [90] showed that the problem of scheduling chains of unit execution time (UET) jobs on uniform processors with communication delays to minimize the makespan is NP-hard in the strong sense. They also presented a heuristic that generates solutions with known and relatively small, absolute error for this problem.…”
Section: Miscellaneous Problem With Preemptive Jobsmentioning
confidence: 99%
“…The resulting scheduling problem (i.e. pre-emptable components executing on machines that differ in their rates of processing-but these rates are constant for the duration of the experiment-with migration overheads) is well defined in the literature on processor scheduling (see Kubiak et al 2002). Thus, we face a known problem in the (new) context of dynamically changing resources and applications (i.e.…”
Section: Experimental Studymentioning
confidence: 99%